DEVELOPING A CULTURE OF HEALTHY LIFE AMONG THE STUDENTS THROUGH TURON WRESTLING (Conferencea, 2021)
In the following the article, the opportunities of Turon wrestling solo s and productive aspects of attracting students and young people to the sport, absorbing and developing the concepts of the culture of healthy living have been studied, technological conditions of the organization of the targeted pedagogical process have been referred to. The propagation of the ideas of modernized version of Turon wrestling is promoted. The advantages of the Turon wrestling are described through the reforms in the Republic of Uzbekistan